Pembuatan Film Pendek Bertemakan Persahabatan “How Bromance Us” - Willy Putranto Kurniawan; Vika Andriani; Tasha Rikayama (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
A good relationship is not always shared by most teenagers especially in socializing, even not just teenagers, the bigger a person, the more difficult it will be for them to have sincere friendships. In the present era there are many bad things that cause a problem and also have a negative impact that starts from a friendship that is not good. According to an extreme statement by British anthropologist Robin Dunbar, we could have hundreds of friends, but no more than 5 could understand us. This statement and phenomenon is the inspiration for this short film work entitled